2017
DOI: 10.1007/5584_2016_182
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection with Influenza Viruses and Influenza-Like Virus During the 2015/2016 Epidemic Season

Abstract: Concerning viral infection of the respiratory system, a single virus can cause a variety of clinical symptoms and the same set of symptoms can be caused by different viruses. Moreover, infection is often caused by a combination of viruses acting at the same time. The present study demonstrates, using multiplex RT-PCR and real-time qRT-PCR, that in the 2015/2016 influenza season, co-infections were confirmed in patients aged 1 month to 90 years. We found 73 co-infections involving influenza viruses, 17 involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Circulation of A(H1N2) viruses genetically similar to the Chinese cases was observed globally in humans in 2000 to 2003 [6]. Dual infections with influenza A subtypes are not unusual [7,8], and pose a risk for reassortment events and the occurrence of new viruses. A special concern is the risk of reassortment events between seasonal and zoonotic viruses, which could result in viruses with pandemic potential [9].…”
Section: Discussionmentioning
confidence: 99%
“…Circulation of A(H1N2) viruses genetically similar to the Chinese cases was observed globally in humans in 2000 to 2003 [6]. Dual infections with influenza A subtypes are not unusual [7,8], and pose a risk for reassortment events and the occurrence of new viruses. A special concern is the risk of reassortment events between seasonal and zoonotic viruses, which could result in viruses with pandemic potential [9].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the A/H3N2/ subtype of influenza virus predominated in Poland during the 2016/2017 season. This finding contrasted with the preceding 2015/2016 season when, although somehow fewer samples were tested, the A/H1N1/pdm09 subtype predominated (Cieślak et al 2017;Kowalczyk et al 2017;Szymański et al 2017a). However, the A/H3N2/ also was a leading subtype in the 2014/2015 season, although it circulated together with the A/H1N1/ pdm09 subtype (Bednarska et al 2016).…”
Section: Resultsmentioning
confidence: 67%
“…In the 2016/2017 season in Poland, there were 11 coinfections of the A/H3N2/subtype with other influenza and influenza-like viruses, particularly found in the elderly and young children (Table 1). In contrast, in the preceding 2015/ 2017 season, the presence of the A/H3N2/subtype was not confirmed in any of the coinfections (Szymański et al 2017a). For comparison, in the past 2014/2015 and 2013/2014 seasons, there were only two and four coinfections recorded with this subtype, respectively, in children up to 14 years (Hallmann-Szelińska et al 2016;Bednarska et al 2015).…”
Section: Resultsmentioning
confidence: 75%
“…This study provides evidence that the heterotypic infection-reinfection occurs at an observable frequency and can lead to severe disease without cross-protection. Moreover, other studies have showed prominent co-infections of influenza A and influenza B viruses [ 104 ]. Further study is needed to understand the mechanisms of immune activation or suppression during sequential heterotypic and co-infections of two influenza virus types.…”
Section: Experimental Animal and Human Studies Of Preimmunitymentioning
confidence: 99%